Precision measurements of the ∧c + and D0 lifetimes - Kushnirenko, A.; Alkhazov, G.; Atamantchouk, A. G.; Balatz, M. Y.; Bondar, N. F.; Cooper, P. S.; Dauwe, L. J.; Davidenko, G. V.; Dersch, U.; Dolgolenko, A. G.; Dzyubenko, G. B.; Edelstein, R.; et al. (American Physical Society (APS), 2001)
A measurement technique of charm baryons lifetimes from hadro-production data was presented. The measurement verified the lifetime analysis procedure in a sample with higher statistical precision. Other effects studied include mass reflections; effects of the presence of a second charm particle; and mismeasurement of charm decays. Monte carlo simulations were used for the detailed study of systematic effects using the charm data.
Keywords: Hydra-production data; Algorithms; Computer simulation; Decay (organic); Maximum likelihood estimation; Monte Carlo methods; Spectrometers; Elementary particles